Peningkatan Hasil Belajar pada Pembelajaran Tematik Terpadu dengan Menggunakan Model Cooperative Learning Tipe Numbered Head Together di Kelas IV SDN 07 Sungai Limau - Yaldi, Novri; Refiarni, Refiarni (Jurnal Pendidikan Nasional, 2021)
The researcher found that: 1) The teacher had not divided the students into several groups and gave different numbers, 2) the teacher had not asked questions to the students, 3) the teacher had not given students the opportunity to think about the answers to the teacher's questions, and 4) the teacher had not given the opportunity to the students. students to provide answers to the teacher's questions. The purpose of the study was to improve student learning outcomes in integrated thematic learning with the Numbered Head Together Cooperative Learning Model in Class IV SDN 07 Sungai Limau. The approach used in this research is a qualitative approach and a quantitative approach. This type of research is classroom action research, which consists of 2 cycles, carried out in 4 stages, namely planning, implementation, observation, and reflection. The technique of this research is observation and test. This research data is in the form of information about the implementation process obtained from observations of lesson plans, teacher aspects, and aspects of students and learning outcomes. The research subjects were teachers and fourth grade students of SDN 07 Sungai nLimau, totaling 13 people. The results showed that planning, implementation and learning outcomes had increased. The RPP assessment in the first cycle was 77.78% with qualification (C) and in the second cycle it increased to 94.4% with qualification (SB). The assessment of the implementation of the first cycle of teacher activities is 79.16% with qualifications (C) and increases to 95.83% in cycles with qualifications (SB). For student activities in the first cycle, 79.16% with qualification (C) increased to 95.83% in cycle with qualification (SB). The assessment of student learning outcomes in the first cycle was 66.42 with qualifications (PB) and increased in the second cycle to 84.83 with qualifications (B). Thus, it can be concluded that the Numbered Head Together Cooperative Learning model can improve integrated thematic learning in elementary schools.